Effectiveness of brodalumab after previous treatment failure of interleukin‐17A inhibitors in patients with psoriasis. Issue 6 (27th August 2021) - Loft, Nikolai; Bregnhøj, Anne; Fage, Simon; Nielsen, Claus Henrik; Enevold, Christian; Zachariae, Claus; Iversen, Lars; Skov, Lone
Abstract: Studies on switch between interleukin (IL)‐17 inhibitors are scarce. We assessed the effectiveness of brodalumab in patients with previous treatment failure of IL‐17A inhibitor(s). Patients with psoriasis and previous treatment failure of an IL‐17A inhibitor were treated with brodalumab at standard dose. Effectiveness was assessed after 12, 26, and 52 weeks of treatment. The primary outcome was the proportion of patients that had achieved an absolute psoriasis area and severity index (PASI) ≤2 and/or a relative reduction of PASI of 75% (PASI75) at week 12. Plasma cytokine levels were measured at baseline and after 12 weeks of treatment. In total, 20 patients were included, seven (35%) were female, the median age was 50 years, and the median baseline PASI was 13.5. Analyzing the data using nonresponder imputation, 14 (70%) patients had achieved either PASI75 and/or PASI ≤2, 8 (40%) had achieved PASI90, and three (15%) had achieved PASI100 at week 12. In total, nine patients (45%) completed the 52‐weeks trial and seven patients (35%) still had PASI75 throughout 52 weeks. Seventeen out of 20 patients experienced any adverse events (AEs) during 52 weeks with no serious AEs or deaths. Patients responding to treatment had lower levels of tumor necrosis factor (TNF)‐α and IL‐6 at baseline compared with those who did not respond to treatment (TNF‐α, p = 0.041, IL‐6, p = 0.0054). In conclusion, treatment with brodalumab despite previous treatment failure with an IL‐17A inhibitor can be effective and well‐tolerated.